2016
DOI: 10.7705/biomedica.v36i2.2953
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo en escenarios emergentes de leishmaniasis visceral urbana, Misiones, Argentina

Abstract: <p><strong>Introducción.</strong> La leishmaniasis visceral es una enfermedad desatendida de alta letalidad que requiere profundizar los estudios locales para un diseño de estrategias de control efectivo. En América se verificó la urbanización de su transmisión, teniendo como reservorio principal al perro doméstico, donde condiciones socio-económicas, representaciones y prácticas de grupos domésticos (GD) jugarían un rol estratégico poco conocido para su endemicidad. <strong>Objetivo.&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
9
0
3
Order By: Relevance
“…Lack of adequate sanitation attracts wild or domestic animals and may be breeding sites for the sandflies. Examples include: Posadas, Argentina, where most individuals with VL also lived in low-quality homes composed of sand floors, wooden walls, partially or totally open roofs and without window screens; 61 Bihar, India, where mud-plastered walls increased the risk of VL two-fold compared to cement walls; 62 and Fulbaria, Bangladesh, where the prevalence of VL was 59% in homes made with mud floors and tin walls. 63 Two studies in Brazil showed that a high incidence of VL was associated with a lack of appropriate sanitation and that low-income individuals resided in high-risk VL areas.…”
Section: Vulnerability To and Risk Factors For Leishmaniasesmentioning
confidence: 99%
“…Lack of adequate sanitation attracts wild or domestic animals and may be breeding sites for the sandflies. Examples include: Posadas, Argentina, where most individuals with VL also lived in low-quality homes composed of sand floors, wooden walls, partially or totally open roofs and without window screens; 61 Bihar, India, where mud-plastered walls increased the risk of VL two-fold compared to cement walls; 62 and Fulbaria, Bangladesh, where the prevalence of VL was 59% in homes made with mud floors and tin walls. 63 Two studies in Brazil showed that a high incidence of VL was associated with a lack of appropriate sanitation and that low-income individuals resided in high-risk VL areas.…”
Section: Vulnerability To and Risk Factors For Leishmaniasesmentioning
confidence: 99%
“…Experiences and lessons learned from the Chinese VL control program have demonstrated that the VL transmission is likely to rebound once the control efforts are weakened [13]. As transmission of VL and the distribution of sandfly populations are greatly affected by natural, biological and social factors [14][15], timely identification of VL cases, and consolidated development and optimization of control strategies, are needed for the interruption and elimination of VL transmission. [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…21 Although we performed a molecular study in just a third of the cases, 87.5% of these were positive for L. infantum. The identification of this species in CL in Argentina is noteworthy, as until now it had caused only LV, [14][15][16] whereas CL was exclusively related to Leishmania braziliensis. 6 Our study, therefore, signals a change in the northwestern region of Argentina, describing an outbreak of CL, caused for the first time by L. infantum.…”
Section: Discussionmentioning
confidence: 91%
“…13 Since then, the species has also been identified as the cause of VL in another four provinces: Salta, Entre Ríos, Santa Fé, and Santiago del Estero. [14][15][16] Thus, L. infantum is present in Argentina as a cause of VL. This study describes the clinical and parasitological characteristics of the first L. infantum-caused CL outbreak in Argentina.…”
Section: Introductionmentioning
confidence: 99%